Shifting feed delivery time: effects on feeding behavior, milk production, and blood biomarkers in late-lactating dairy cows - Cattaneo, Luca; Passamonti, Matilde Maria; Piccioli-Cappelli, Fiorenzo; Trevisi, Erminio (Frontiers in Animal Science, 2024)
Improving the synchronization between the pattern of milk synthesis and nutrient availability throughout the day could enhance production efficiency. In this study, we evaluated the effects of changing feed delivery time on milk production, feeding behavior, and the daily rhythms of blood biomarkers. Eight multiparous Holstein cows housed in a tie-stall barn with controlled environmental conditions were enrolled in a crossover experimental design with three periods of 14 days and three treatments each. Cows were milked twice daily (0530 and 1730 h) and were individually fed with two equal meals of forage and eight equal meals of concentrate during the day. Forage meals were provided at 12-hour intervals either: (i) 5 h before each milking (0030 and 1230 h; BM), (ii) at the end of each milking (0530 and 1730 h; ME), (iii) or 2 h after (0730 and 1930 h; AM). Feed intake and feeding behavior were monitored, and milk production and composition were measured. Blood samples were collected every 4 days at 0700 h and, during the last day of each period, 15 times daily to determine metabolic profiles, hormones, and their daily rhythmicity by the cosinor analysis. Changing forage delivery time did not affect milk yield and dry matter intake. No difference was observed in feeding behavior when expressed relative to the first meal. There were no significant differences in milk component contents and yields. In samples collected at 0700 h, ME had reduced plasma calcium (Ca), magnesium (Mg), and potassium (K) and increased sodium (Na). AM had increased inflammation, as suggested by the greater blood globulin and ceruloplasmin. The patterns of metabolic biomarkers had limited variations when expressed relative to the first forage meal. Nevertheless, the daily rhythms of these biomarkers were remarkably different. Under our conditions, feeding forage meals to cows at different times of the day did not influence productive performance but highlighted the importance of considering the sampling time when interpreting metabolic profiles.